Respons Pasar Modal Indonesia Terhadap Pengumuman Insentif Fiskal Biaya R&D Korporat - Hanindipto, Fasa Aditya; Suroso, Arif Imam; Andati, Trias (School of Business, Bogor Agricultural University (SB-IPB), 2022)
This study examines the Indonesia stock market’s response to the announcement of tax deduction as an incentive for corporate R & D activity implementation. The study is performed using samples of 13 companies from Miscellaneous Industry and Consumer Goods Industry in Indonesia Stock Market June – July 2019 period. This study uses event study approach, by examining market reaction calculated by Cumulative Abnormal Return (CAR), Cumulative Abnormal Volume (CAV), and Cumulative Abnormal Frequency (CAF). To measure the significance of each variable, non-parametric statistic test Wilcoxon Signed Rank Test and Mann Whitney Test are performed. The Result shows that investors respond to the announcement of tax deduction as an incentive for Indonesia corporate R & D activity. Another result shows that there are different responses from Miscellaneous Industry and Consumer Goods Industry sectors in the Indonesia Stock Market. Keywords: Corporate R & D, event study, fiscal policy, tax deduction